Block Scheduling Report: Review and Recommendations
As CSUB approached completion of the Block Scheduling Pilot, the Block Scheduling Continuation Workgroup was formed and charged with developing a plan for implementing Block Scheduling with 100% of first-time freshmen. While addressing the issues of sustainability and workload, the workgroup was charged with creating a plan that would preserve the following goals of Block Scheduling: •Students take 15 units per semester •Students take courses following their major roadmap •Learning communities are developed and maintained